Effect of intense interval workouts on running economy using three recovery durations - Zavorsky, G. S.; Montgomery, D. L.; Pearsall, D. J. (European Journal of Applied Physiology, 1998)
This study showed that RE (running economy) can be perturbed after a high-intensity interval workout and that the changes in V˙O2 (oxygen consumption), HR (heart rate) and R (respiratory exchange ratio ) were independent of the recovery duration between the repetitions.